Migration, Population Composition and Long Run Economic Development: Evidence from Settlements in the Pampas - Droller, F (Blackwell Publishing Ltd, 2018)
This article analyses the impact of population composition on long run economic development, by studying European migration to Argentina during the Age of Mass Migration (1850–1914). I use an instrumental variables (IV) approach that assigns immigrants to counties by interacting two sources of variation: the availability of land for settlement and the arrival of Europeans over time. Counties with historically higher shares of European population in 1914 have higher per capita GDP 80 years later. I show that this long run effect is linked to the higher level of human capital that immigrants brought to Argentina. I show that Europeans raised literacy rates in the receiving counties, and that high-skilled Europeans played an important role in the onset of industrialisation, owned most of the industrial establishments, and provided the majority of the industrial labour force. © 2017 Royal Economic Society